The society of the disposable and other vicissitudes of the postmodern world - Arboccó de los Heros, Manuel (2017)
In the past thirty or forty years, approximately postmodern society points out a particulartime fraught with changes and distinctive characteristics in social, moral, economic andcultural aspects. In general terms, it is a society with a high level of production and massconsumption, where technology is pervading, and media figures pop up and disappear(small idols); a society with a rampant relativism, a plurality of options of all kinds, a callinginto into question (if not fall) of great dogmas, a culture of the image along with a defenseof individualism and sometimes a misunderstood “Psychology of success”, as well as analmost obsessive quest for happiness that is in contrast to high levels of anxiety, stress andexistential vacuum. In sum, a complex society as always have been human societies but thathas broken in a short time a lot of the classic and traditional. With their possibilities andwith their tragedies, like many others. We present this small essay on the culture of thesetimes, in the hope, as always, of contributing to the academic debate